Incidence and survival of childhood central nervous system tumors in Denmark, 1997–2019. (19th November 2021) - Helligsoe, Anne Sophie Lind; Kenborg, Line; Henriksen, Louise Tram; Udupi, Aparna; Hasle, Henrik; Winther, Jeanette Falck
Abstract: Background: Incidence rates in Denmark of central nervous system (CNS) tumors remain among the highest in the world. Survival rates, however, have improved in the past decades in high‐income countries. Methods: We analyzed incidence and survival of childhood CNS tumors in Denmark diagnosed from 1997 to 2019 based on data from the Danish Childhood Cancer Registry and information on histological types, tumor localization, and treatment from medical records. Results: From 1997 to 2019, 949 children<15 years were diagnosed with a CNS tumor. Age‐standardized incidence was 42.1 (95% CI, 39.4–44.6) per million person‐years and stable during this period. Age‐specific incidence for children aged 0–4 years was 47.7 per million. More than one‐third ( n = 374, 39.4%) were treated with surgery alone. Overall survival rates 5 and 10 years after diagnosis were 77.6% (95% CI, 74.7–80.2) and 74.7% (95% CI, 71.7–77.5). Five‐year overall survival improved from 73.0% (95% CI, 68.9–76.7) in 1997–2008 to 83.2% (95% CI, 79.2–86.4) in 2009–2019 ( p ‐value < 0.0001) in children aged 0–4 years ( p = 0.0006). Conclusion: Incidence rates are stable but remain among the highest in the world. Despite improved survival rates in recent years in younger children, some subtypes still have a poor prognosis. Abstract : Incidence of childhood central nervous system (CNS) tumors in Denmark from 1997 to 2019 was 42.1 per million person‐years and did not increase from 1997 to 2019. Survival has improved especially among younger children with CNS tumors. Still, some subgroups in particular have a poor prognosis.